A Gynocritical Analysis of Newman's Julia as a Response to Orwell's Nineteen Eighty-Four - Onvural, Sena (Istanbul Univ, Fac Letters, 2025)
Elaine Showalter believes it is restrictive to read stories about women written by male writers because male-dominated narration is filled with stereotypical representations of women, which consequently maintains the victimization of women. With her idea of gynocriticism, she refers to the need for female writers to write about the female. In that sense, she demands female characters to be put at the centre of literary works in order to reach a more inclusive understanding of human experience. Building on her theory of female writing, this paper attempts to show that female experience, perspective, and voice must be communicated within the literary landscape to have a better and multifaceted understanding of the lives of women and to fix the misinterpretations of womanhood through the analysis of Julia 2023 by Sandra Newman and Nineteen Eighty-Four 1949 by George Orwell. Even though Orwell manages to critique the horrible outcomes of totalitarianism in his canonical dystopia through his protagonist Winston, he completely ignores what Julia feels, thinks, or experiences. There is not much information about Julia's life as an individual or as a woman. Therefore, Newman reconstructs Julia as the protagonist of her dystopia by focusing solely on Julia's thoughts, endeavours, and emotions by filling in the missing parts that Orwell does not touch upon. Accordingly, this paper examines how a female writer establishes a society that is not solely governed by universally accepted male-dominated ideals, creating a space for a formerly silenced and decentralised character so that she can be valued on her own terms.
Keywords: Showalter; gynocriticism; Julia; feminist criticism; female writing